PENGARUH FEE BASED INCOME, SPREAD BAGI HASIL, DAN FINANCING TO DEPOSIT RATIO TERHADAP PROFITABILITAS - Alfiyani Barokah; Annio Indah Lestari Nasution; Nurul Jannah (ITB AAS Indonesia Surakarta, 2024)
The goal of the study is to determine how the profitability of the Shariah general bank (BUS), which is anticipated to provide a return on assets, is impacted by fee-based income, spread for income, and financing to deposit ratio. (ROA). Descriptive quantitative research is the term for this kind of study. Data from the SBH, FBI, FDR, and ROA BUS for the years 2015 to 2022 are used as secondary data in the form of time series or time rows. The Financial Services Authority (OJK) website's Statistics of the Shariah General Bank provided the information. Purposive sampling was used to choose the sample for this investigation (based on criteria). Six Shariah General Banks (BUS) with OJK registration, namely BJBS, BMI, BMS, BSB, BCAS, and BTPN shariah, were utilized as samples. The study's findings demonstrate that the financing to deposit ratio, fee-based revenue, and spread for income collectively have a favorable and significant impact on the profitability (ROA) of Sharia banking at the Sharia General Bank in Indonesia. Keywords : Fee based Income, Spread to Profit, Financing to Deposit Ratio, Profitability